Towards an Understanding of Technical Debt in Reference Architectures - Damaceno, Katia; Nakagawa, Elisa; Braga, Rosana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Reference architectures refer to a special type of software architecture that has supported the development, evolution, and standardization of software systems in several critical domains. However, important decisions made while designing a reference architecture can lead to technical debt (TD). Even though the academy is investing efforts in the last decade to understand the problems implied by TD in the architectural level (known as architectural technical debt - ATD), it has not been addressed in the level above, i.e., in the reference architecture level. This paper introduces an understanding of TD in reference architectures and, through a systematized research method, proposes a definition for reference architecture technical debt (RATD) and its corresponding conceptual model. RATD could draw the attention from the community about the need of managing architectural debts found in most reference architectures.